Indonesia's Defense Strategy Against Transnational Crimes of the Abu Sayyaf Group in the Sulu Archipelago - Titis Margiati; Mhd Halkis; Rudy Sutanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Southeast Asia, especially Indonesia, is a region where there are many cases of attacks by armed pirate groups. One of the points is in the Sulu Sea which is included in the territorial waters of the Philippines. The waters of the Sulu Sea are directly adjacent to several areas of Indonesia, namely Kalimantan and Sulawesi, so it is not surprising that terrorist groups from the Philippines carry out acts of piracy/jacking of ships originating from Indonesia. The Abu Sayyaf group, which started its criminal activities in the 1990s, hijacked slow-vehicle loaded ships and took hostage crew members who passed through the area. This paper will be prepared using a qualitative descriptive method. This paper will focus more on explaining and providing an overview of the forms of defense strategy carried out by Indonesia in dealing with the problem of transnational crimes by the Abu Sayyaf group. This research data was obtained based on literature review sourced from previous research in the form of journals, books and other scientific works that are relevant to the topic of discussion. The result of this paper is that the Abu Sayyaf Group threat is asymmetrical, coming from non-state actors facing state actors. The Abu Sayyaf group has an interest in establishing an Islamic state in the Philippines and to maintain the existence of its group, the Abu Sayyaf group takes hostage actions by asking for ransom. In order to deal with these non-military threats, the Indonesian national defense strategy is not only carried out by means of the military, but is carried out by relying on 3 (three) main pillars, namely the use of defense force, international cooperation, and the development of defense forces. In facing the threat of the Abu Sayyaf Group, Indonesia has prioritized the pillars of international cooperation even though there have been options for the development and use of defense forces and also the development of defense forces as a deterrent factor to minimize threats.